EVALUATION OF THE QUALITY OF POTATOES (Solanum Tuberosum L) IN A DIFFERENT GROWING ENVIRONMENT - Suryaningsih, Dwie Retna; Thohiron, ⁠Mochamad; Hassan, ⁠Faez M.; Sa'adah, ⁠Tatuk Tojibatus; Ang, ⁠Ken William; Akbar, ⁠Moch. Alifi (Yayasan Education and Social Center, 2024)
The purpose of this study is to evaluate the quality and hedonic traits of potatoes grown in a variety of environments. The study was conducted between June and July 2023 in Batu, Bromo, and Nongkojajar. After the harvest, research data was gathered, including the tubers' weight, volume, length, and width. The tubers are steamed after three days to evaluate their taste, smell, colour, texture, and overall physical appearance. Data analysis methods use bivariate, multivariate analysis and PCA biplot with spreadsheets and SAS-JMP v.16. The quality of potato tubers was found to vary significantly between different growing environments in terms of length, width, thickness, volume, and weight per tuber. The superior quality of tubers for all categories is produced in Batu's growing environment, which is markedly different from Bromo and Nongkojajar. The high correlation between length, volume and weight of tubers is more than 0.83. Organoleptically, each growing environment has a position of relative advantage. Stone has advantages in smell and physical appearance. Bromo is superior in texture and colour, with a high correlation of 0.98, and Nongkojajar in taste. Based on the level of consumer preference, it can be concluded that Batu is superior in terms of its physical appearance, Bromo is superior in terms of colour, and Nongkojajar is superior in terms of smell. Even though there was a high correlation of 0.995 between the various growing locations, none of them demonstrated superiority in terms of texture and taste